FRI0222 Sustained response following discontinuation of methotrexate in patients with rheumatoid arthritis treated with subcutaneous tocilizumab: results from a randomized controlled trial (COMP-ACT). (15th June 2017) - Kremer, J; Rigby, W; Singer, N; Birchwood, C; Gill, D; Reiss, W; Pei, J; Michalska, M
Abstract : Background: Methotrexate (MTX) is frequently administered in combination with biologics for the treatment of rheumatoid arthritis (RA). MTX may be subsequently discontinued due to intolerance or nonadherence, and/or to reduce medication burden once disease control is achieved. Previous studies have established the efficacy of tocilizumab (TCZ) initiated as monotherapy (MONO), but the impact of MTX withdrawal in patients achieving good clinical response to TCZ+MTX (COMBO) has not been evaluated. Objectives: To evaluate whether TCZ-MONO is non-inferior to TCZ-COMBO in maintaining clinical response in patients who achieve low disease activity with TCZ-COMBO. Methods: US patients with RA who were inadequate responders to MTX were enrolled: initial combination therapy included MTX (15 mg/week orally) plus TCZ 162 mg subcutaneous (SC) either weekly (qw; for patients ≥100 kg) or every 2 weeks (q2w; for patients <100 kg). Dose escalation from q2w to qw was allowed at week 12 in patients who had not achieved low disease activity (DAS28 ≤3.2). If patients achieved DAS28-ESR ≤3.2 at week 24, they were randomized (double-blind) 1:1 to receive either TCZ-MONO or continue TCZ-COMBO until week 52. Patients who did not achieve DAS28 ≤3.2 were assigned to an open-label arm and continued TCZ-COMBO until week 52. The primary outcome measured was the comparison of mean change in DAS28-ESR score in the randomized cohort between weeks 24 and 40, between the TCZ-MONO or TCZ-COMBO arms (noninferiority margin of 0.6). Secondary outcomes included the proportion of patients achieving DAS28 <2.6, DAS28 ≤3.2 and American College of Rheumatology 20%/50%/70% (ACR20/50/70) responses at weeks 40 and 52, and safety. Trial registration number: NCT01855789 . Results: Of 718 patients enrolled, 296 were randomized at week 24 (TCZ-MONO, n=148; TCZ-COMBO, n=148). Early discontinuation in the randomized cohort occurred in 12.2% of patients in the TCZ-MONO group and 10.2% in the TCZ-COMBO group. Baseline characteristics were balanced between treatment groups (mean age 55.5 years; 74.8% female; mean RA duration 6.8 years; mean DAS28-ESR 6.3). At week 24, DAS28 scores were similar in both groups, but ACR responses were ∼8–11% lower in the TCZ-MONO group prior to MTX withdrawal (randomization). The mean change in DAS28 was similar between the randomized treatment groups (Table 1 ). For the primary efficacy analysis, the mean changes in DAS28 from week 24 to week 40 were 0.46 and 0.14 in the TCZ-MONO and TCZ-COMBO groups, respectively (95% CI: 0.045–0.592). This study met the primary endpoint by demonstrating that discontinuing MTX in TCZ responders was noninferior to continuing MTX. The safety of TCZ-SC in this study was consistent with the known safety profile with no new safety signals observed (Table 2). The most common SAE was infection, occurring in 4.1% of patients. TCZ-COMBO had greater frequency of AEs, SAEs and serious infections than TCZ-MONO. Conclusions: These results demonstrate that patients receiving TCZ-COMBO who achieve low disease activity can discontinue MTX and maintain disease control. Acknowledgements: This study was funded by F. Hoffmann-La Roche, Ltd. Disclosure of Interest: J. Kremer Shareholder of: Corrona, LLC, Consultant for: AbbVie; Amgen; Bristol-Meyers Squibb; Genentech; GlaxoSmithKline; Eli Lilly; Pfizer; Regeneron; Sanofi, Employee of: Corrona, LLC, W. Rigby Consultant for: Roche, N. Singer Grant/research support from: Merck, EMD Serono, Consultant for: Pfizer, C. Birchwood Employee of: Genentech, Inc., D. Gill Employee of: Genentech, Inc., W. Reiss Employee of: Genentech, Inc., J. Pei Employee of: Genentech, Inc., M. Michalska Employee of: Genentech, Inc.